2018
DOI: 10.1111/jpy.12757
|View full text |Cite
|
Sign up to set email alerts
|

Different fermentation strategies by Schizochytrium mangrovei strain pq6 to produce feedstock for exploitation of squalene and omega‐3 fatty acids

Abstract: Schizochytrium mangrovei strain PQ6 was investigated for coproduction of docosahexaenoic acid (C22: 6ω-3, DHA) and squalene using a 30-L bioreactor with a working volume of 15 L under various batch and fed-batch fermentation process regimes. The fed-batch process was a more efficient cultivation strategy for achieving higher biomass production rich in DHA and squalene. The final biomass, total lipid, unsaponifiable lipid content, and DHA productivity were 105.25 g · L , 43.40% of dry cell weight, 8.58% total l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Many studies have confirmed that Aurantiochytrium sp. could accumulate a considerable amount of squalene (Jiang et al, 2004; Chen et al, 2010; Fan et al, 2010; Kaya et al, 2011; Hoang et al, 2014, 2018; Nakazawa et al, 2014). In a patent (WO/2012/159979) registered for discovering a process for producing squalene from the microalgal species Thraustochytriales , claimed that by providing an enriched medium with vitamins B 12 , B 1 and/or B 6 at 30°C temperature, squalene titre could be obtained between 20 and 120 mg/g DCW (Pora et al, 2014).…”
Section: Natural Sources Of Squalenementioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have confirmed that Aurantiochytrium sp. could accumulate a considerable amount of squalene (Jiang et al, 2004; Chen et al, 2010; Fan et al, 2010; Kaya et al, 2011; Hoang et al, 2014, 2018; Nakazawa et al, 2014). In a patent (WO/2012/159979) registered for discovering a process for producing squalene from the microalgal species Thraustochytriales , claimed that by providing an enriched medium with vitamins B 12 , B 1 and/or B 6 at 30°C temperature, squalene titre could be obtained between 20 and 120 mg/g DCW (Pora et al, 2014).…”
Section: Natural Sources Of Squalenementioning
confidence: 99%
“…In the experiment, a squalene content of 33 mg/g DCW was recovered for both cases, while the yields reached 0.99 and 1.01 g/L, respectively (Hoang et al, 2014). Recently, this strain was analyzed for different fermentation conditions, wherein the maximum squalene content (98.07 mg/g of lipid) was attained after 48 h of incubation in a 15 L medium containing 22% glucose (Hoang et al, 2018). High squalene producing novel yeast-like fungus strain Pseudozyma SD301 has also been isolated.…”
Section: Fermentation Optimization For Squalene Productionmentioning
confidence: 99%
“…In the first trial, this basal medium was compared to MT1, a culture medium that was designed in accordance with the information available in the literature [2,6,10,11,14,17,20,[26][27][28][29][30][31][32][33][34]. The MT1 medium was tested using two trace metals solutions: (i) TM1, the trace metals solution of MB10; and (ii) TM2, formulated based on previous results obtained in the literature [6,8,10,14,16,17,20,24,26,27,[32][33][34][35].…”
Section: Effect Of Basal Culture Medium and Trace Metals Solutionmentioning
confidence: 99%
“…DHA belongs to a class of LC-PUFA often called "omega-3 fatty acids", which are in high demand due to the many known benefits in nutrition. DHA is also widely known for its fundamental role in preventing cardiovascular diseases, being essential for brain and eye development (particularly in children), learning capacities, as well as for the prevention of neurodegenerative conditions, arthritis, asthma and skin diseases [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. In addition, DHA plays a key role in membrane fluidity, cell signaling, cell interactions and in the development of the immune system and inflammatory responses [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation